12. Lipid profile in the Blood of the Sumatran Elephant (Elephas maximus sumatranus) in Elephant Conservation Center (ECC) Saree, Aceh Besar - mahmudi kamaruddin; Al Azhar; Arman Sayuti; Zuhrawati Zuhrawati; Nuzul Asmilia; Sri Wahyuni (Jurnal Medika Veterinaria, 2017)
This study was done to investigate lipid profile in the blood of Sumatran elephants at the ECC of Saree. In this stud blood samples were drawn from the auricular vein of 8 sumatran elephants at the ECC. Reasurement of total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), and triglicerida (TG) was carried spectrophotometrically by the commercial service of research laboratory in Banda Aceh. The results showed that the average concentrations of total cholesterol, LDL, HDL, and TG in the blood of Sumatran elephants were 155,86±54,39 mg/dL, 40,13±3,40 mg/dL, 101,13±46,16 mg/dL, dan 84,89±32,86 mg/dL. It can be concluded that the average concentrations of the lipid profile in the blood of the sumatran elephants at the ECC in Aceh were higher than that of reported in other subspecies of Asian elephant